Non-linear tree height (h-d) model development and forest resource productivity assessment of Diguyo limestone forest within Northern Sierra Madre Natural Park - Doyog, Nova D.; Lumbres, Roscinto Ian C.; Weerd, Merlijn van; Baoanan, Zenaida G. (Philippine journal of science)
"Forest resource monitoring of different forest types is of great importance in sustainable forest management and climate change mitigation. Monitoring the productivity of forest resources could be achieved by modeling the basic tree parameters necessary for forest growth and yield. This study was conducted to develop a height-diameter at breast height (h-d) model necessary for tree height (h) estimation since h measurement is difficult in the field, especially in dense forests, and to estimate the forest productivity of the Diguyo limestone forest within the Northern Sierra Madre Natural Park (NSMNP)" - title page.